COMMUNICATIVE ASPECTS OF MULTILINGUAL CODE SWITCHING IN COMPUTER-MEDIATED COMMUNICATION - Caparas, Pilar; Gustilo, Leah (Universitas Pendidikan Indonesia, 2017)
The quintessential role of language has been punctiliously studied relative to intercultural communication, cultural heritage, social development, education, identity construction and many more domains. One forum wherein language is investigated is the Computer-mediated Communication (CMC) which provides a fertile ground for linguistic and sociolinguistic analyses. The present study aims at investigating the preferred codes used in code switching (CS), functions of CS, and the motives of users for employing CS in CMC. The present study was based on the investigation of 200 status updates and 100 wall posts of 50 Facebook accounts of students who are enrolled in a leading state university in Mindanao and professionals who graduated from the same university. Besides English and Filipino, these Facebook users speak various regional languages such as Chavacano, Cebuano, and Tausug. Their posts were analyzed employing eclectic approaches in analyzing inter-sentential and intra-sentential code switching. The findings reveal that the preferred code in their online communication is Taglish. It implies that Taglish is an equalizer, non-privileging, non-discriminating, and more unifying. The primary reason for CS is because of real lexical need. Besides the given categories, the study determined four other reasons for CS, namely: to express ideas spontaneously, to retain native terminology, to express disappointment, and to promote relationship. The findings vouch for the viability of regional languages to co-exist with English and other languages in the gamut of human interactions in the internet.